INFLUENCE OF CONTEXTUAL FACTORS ON INTENTION OF ENTREPRENEURSHIP - Tegowati, Tegowati; Palupi, Dian; Rochdianingrum, Widhi Ariestianti (UNIPA PRESS, 2019)
One way to improve the competence of college graduates can be done by giving motivation to students to become entrepreneurs. In addition to improving student competency, entrepreneurship is also one of the efforts of universities to reduce the unemployment rate of college graduates. For this reason, interest in entrepreneurship among academics must be increased because it has a large contribution to the progress of a nation. This study aims to review the interests of student entrepreneurship from contextual factors.The population in this study were students in Surabaya with a sample size of 100. The sampling technique used was accidental sampling and data analysis using SEM. The results of this study are: There is a positive and significant influence of contextual factors on the interest in entrepreneurship. Based on the standardized results the parameter coefficient of 0.955 is significant at 0.001 (p = ***).